Self and Complementary Mating Of Carbon-Carbon and Carbon-Carbon-Silicon Carbide Composites in Reciprocating Tribo-Interactions - Kumar P.; Srivastava V.K.; Kumar D.; Sharma S.M. (My University, 2025)
The counter-surface (CS) material during tribological interactions significantly affects the prevalent wear and friction mechanisms, and correspondingly tribological behaviour. Although disparate uni-phase (i.e., single constituent) counter-surface materials exhibit contrast tribological phenomena, the presence of multi-phase (i.e., multiple constituents) CS may further complex the tribological analysis. The complexity of tribo-system further increases in the presence of two multi-phase materials rubbing against each other. Thus, the present article aims to investigate the reciprocating sliding of carbon-carbon (C/C) and carbon-carbon-silicon carbide (C/C-SiC) composites in self and complementary mated pairs with variation of laminate orientation (i.e., normal and parallel orientation of laminates) and normal load. The results indicate that C/C and C/C-SiC complementary mated pair exhibited coefficient of friction (COF) in between the COF of C/C and C/C-SiC self-mated pairs, whether used in parallel/parallel or normal/parallel combinations. Wear loss exhibited by C/C composites in complementary mated pair was higher than wear loss of C/C composites in self-mated pair. The synergism between debris retention in between the interacting surfaces, friction film formation, extent of ploughing effect and repeated flexion in opposite direction dictated the tribological behavior of C/C and C/C-SiC composites in reciprocating sliding. © 2022 Published by Faculty of Engineering.